Methionine in Proteins: It’s not just for protein initiation anymore - Lim, Jung Mi (Neurochem Res, 2018)
Methionine in proteins is often thought to be a generic hydrophobic residue, functionally replaceable with another hydrophobic residue such as valine or leucine. This is not the case, and the reason is that methionine contains sulfur that confers special properties on methionine. The sulfur can be oxidized, converting methionine to methionine sulfoxide, and ubiquitous methionine sulfoxide reductases can reduce the sulfoxide back to methionine. This redox cycle enables methionine residues to provide a catalytically efficient antioxidant defense by reacting with oxidizing species. The cycle also constitutes a reversible post-translational covalent modification analogous to phosphorylation. As with phosphorylation, enzymatically-mediated oxidation and reduction of specific methionine residues functions as a regulatory process in the cell. Methionine residues also form bonds with aromatic residues that contribute significantly to protein stability. Given these important functions, alteration of the methionine-methionine sulfoxide balance in proteins has been correlated with disease processes, including cardiovascular and neurodegenerative diseases. Methionine isn’t just for protein initiation.